Clinical importance of personality difficulties: diagnostically sub-threshold personality disorders - Max Karukivi; Tero Vahlberg; Kalle Horjamo; Minna Nevalainen; Jyrki Korkeila (My University, 2022)
Conclusions
An elevated severity level of personality disturbance is associated with an increase in psychiatric morbidity and social dysfunction. Diagnostically sub-threshold personality difficulties are of clinical significance and the degree of impairment corresponds to actual personality disorders. Since these two groups did not significantly differ from each other, our findings also highlight the complexity related to the use of diagnostic thresholds for separate personality disorders.